Pushing the Canvas / Nicola Setari, Thibaut Verhoeven. - Bezzan, Cécilia; Braeckman, Inge; Demeester, Ann; Eeckhout, Tanguy; Gielen, Denis; Kint, Johanna; Kusters, Liesbet; Kwakkenbos, Lars; Lambrecht, Luk; Leemans, Koen; Lorent, Claude; Lumpkin, Libby; et al. (Mechelen : Cultuurcentrum Mechelen, 2007)
Annerel, Stefan ; Bailly, Virginie ; Balleux, Stephan ; Beaudry, Charlotte ; Cum* ; De Meutter, Ellen ; Degand, Pieter ; Desmet, Stief ; Driesen, Stef ; Heck, Kati ; Huyghe, Thomas ; Lecompte, Wannes ; Liekens, Tom ; Lizein, Annick ; Ronsse, Matthieu ; Stallaerts, Helmut ; Taran, Oxana ; Verhulst, Nicolas ; Vosters, Vadim ; Wright, Cindy
Pushing the Canvas, Cultuurcentrum Mechelen, 2007-05-12. 2007-07-08
boek